The status of knowledge, attitude and practice towards emergency management of avulsed tooth among dental students. a single center cross-sectional study - Muhammad Muzzamil; Hana Pervez; Irum Naz; Raza, Shaeroz (Journal of the Pakistan Medical Association, 2022)
Objective: To evaluate the awareness of emergency trauma management and the potential role of dentists in handling tooth avulsion injuries. Method: The cross-sectional study was conducted at the Dental outpatients department of Jinnah Medical and Dental College, Karachi, from December 2020 to March 2021, and comprised dentists and final year dental students of either gender. Data was collected using a 17-item questionnaire to assess the awareness level regarding the knowledge of traumatic dental emergencies and the role of a dentist in handling a traumatic tooth injury. Data was analysed using SPSS 20. Result: Of the 170 subjects, 52(30.5%) were males and 118(69.4%) were females. Overall, 139(81.8%) subjects had prior knowledge regarding avulsion, 164(96.5 %) were aware of the term avulsed tooth, 106(62.4%) considered milk to be the best transport media for an avulsed tooth, 159(93.5%) knew the significance of extra-oral time, and all 170(100%) subjects said they wanted to study more about dental traumatic injuries. Conclusion: There was adequate knowledge about the term avulsion, transport media and extra-oral time, and there was evidence of interest about learning more among the subjects. Key Words: Avulsion, Emergency handling, Dental trauma, TDIs, Traumatic dental injuries, Knowledge, Appropriate management, Expert.